Workplace Conflict: Its Impact on Employee Motivation and Productivity - Irwan, Irwan (Fakultas Ekonomi, Universitas Muslim Indonesia, 2024)
This study aims to investigate the impact of workplace conflict on employee motivation and productivity, focusing on the distinct effects of interpersonal, task-related, and process-related conflicts. The research explores how effectively managed conflicts can foster positive outcomes, such as innovation and team collaboration while mitigating their negative consequences. A systematic literature review (SLR) approach was employed to synthesize findings from recent studies, providing a comprehensive understanding of workplace conflict dynamics. The study draws from multiple peer-reviewed sources to analyze the relationship between conflict types, employee behavior, and organizational performance. The findings reveal that interpersonal conflicts negatively affect employee motivation by increasing stress and disengagement, while task-related conflicts, when managed constructively, can enhance creativity and problem-solving. Process conflicts have varied impacts, potentially disrupting efficiency and improving work coordination when resolved effectively. Additionally, unresolved conflicts are linked to higher turnover rates and diminished organizational stability. The discussion highlights the dual nature of conflict, emphasizing the importance of proactive conflict resolution strategies in fostering a productive work environment. This research underscores the practical need for organizations to implement effective conflict management mechanisms, such as mediation and communication training. Managerially, leveraging task conflicts for innovation while addressing interpersonal and process conflicts can improve team cohesion and organizational performance. The study contributes valuable insights for developing sustainable conflict resolution practices that support employee well-being and organizational success.